Analisis Pembangkit Listrik Sistem Hybrid Grid Connected Di Villa Peruna Saba, Gianyar – Bali - Arifin Sinaga, Gordon; Mataram, I Made; Indra Partha, Tjok Gede (Jurnal SPEKTRUM, 2019)
Renewable energy is energy that comes from natural processes that will not be exhausted and sustainable if managed properly. In its use, to maintain the continuity of the availability of electrical energy maximally, it is necessary to combine several types of power plants that are connected to the grid or better known as hybrid grid connected power systems. This research took place at Villa Peruna Saba, Gianyar - Bali which uses a hybrid grid connected power system that combines photovoltaics and generators connected to the grid utilty in supplying electricity loads. The analysis is carried out on the characteristics of the average load, the contribution of each electric power source and the workings of the hybrid grid connected hybrid power plant system. From the analysis, it is known that the contribution of power derived from solar power plants is 561.27 kW or 22.41% in April 2018 and 510.72 kW or 20.71% in May 2018.